Standard operation procedures: systematic special equipment reservation system at UiTM Cawangan Negeri Sembilan - Abdullah, Siti Nur Fadzilah; Mohd Johan, Noor Hilmi; Mohd Shah, Nurul Nisha; Hamdan, Efina; Ramli, Noryusnita; Manshor, Maizura (Universiti Teknologi MARA, Kedah, 2023)
Standard operating procedures (SOPs) play a crucial role in controlling human errors and ensuring efficient and safe operations in various industries. This article explains the relationship between SOPs and human error control, highlighting their significance in mitigating errors and promoting a culture of systematic processes. Through a review of existing literature, the article explores the key elements of effective SOPs and their impact on reducing human errors. Additionally, it examines strategies for designing and implementing SOPs that incorporate human factors considerations to enhance their usability and effectiveness. The findings emphasize the importance of clear and concise SOPs, training programs, and ongoing evaluation and revision processes in minimizing human errors. By implementing robust SOPs and integrating human error control measures, organizations can enhance operational reliability, and organizational workflow, optimize performance, time, resource, and costsaving as well as foster a culture of systematic processes. The article concludes with recommendations for future research and practical implications seeking to optimize their SOPs to effectively control human errors.